Tingkat Kemampuan Teknik Shooting Pada Peserta Ekstrakurikuler Futsal Smk Tamtama Karanganyar Kebumen - Puput Widodo; Ginanjar Adi Irawan (Departement of Mathematics Education, 2023)
Sport is an inseparable part of human life. This is because exercise is an important element in maintaining a healthy body. Sports extracurricular activities are one of the programs of the school as the development of sports achievements so that regeneration of achievements is always created and takes place in school activities so that they are well developed and supervised. Futsal is the most popular sport and is loved by Indonesian people, especially men from children, adolescents and adults. This is evident from the fact that people in both urban and rural areas are more fond of futsal than others. In the game of futsal required skills that must be owned by every player. The techniques in futsal are the same as those in football games, starting from passing, dribbling, control, chipping and shooting techniques. Shooting is a part of the most important technique in the game of futsal because this technique must be mastered by the players. A player must master the basic skills of kicking the ball and further improve the accuracy of shooting and scoring goals from various positions on the field. The type of research used is descriptive quantitative using survey methods. The population used is extracurricular participants at SMK Tamtama Karanganyar Kebumen. The number of samples in this study were 20 people. The variables of this study are physical conditions and basic techniques. Data analysis in this study used percentage descriptive data analysis